Combined Use of High-Sensitive Cardiac Troponin, Copeptin, and the Modified HEART Score for Rapid Evaluation of Chest Pain Patients. (12th November 2018) - Morawiec, Beata; Przywara-Chowaniec, Brygida; Muzyk, Piotr; Opara, Mariusz; Ho, Lam; Tat, Lui Chun; Muller, Olivier; Nowalany-Kozielska, Ewa; Kawecki, Damian
Abstract : Background. Clinical short-term risk stratification is a recommended approach in patients with chest pain and possible acute myocardial infarction (AMI) to further improve high safety of biomarker-based rule-out algorithms. The study aim was to assess clinical performance of baseline concentrations of high-sensitivity cardiac troponin T (hs-TnT) and copeptin and the modified HEART score (mHS) in early presenters to the emergency department with chest pain. Methods . This cohort study included patients with chest pain with onset maximum of 6 h before admission and no persistent ST-segment elevation on electrocardiogram. hs-TnT, copeptin, and the mHS were assessed from admission data. The diagnostic and prognostic value for three baseline rule-out algorithms: (1) single hs-TnT < 14 ng/l, (2) hs-TnT < 14 ng/l/mHS ≤ 3, and (3) hs-TnT < 14 ng/l/mHS ≤ 3/copeptin < 17.4 pmol/l, was assessed with sensitivity and negative predictive value. Primary diagnostic endpoint was the diagnosis of AMI. Prognostic endpoint was death and/or AMI within 30 days. Results . Among 154 enrolled patients, 44 (29%) were classified as low-risk according to the mHS; AMI was diagnosed in 105 patients (68%). For ruling out AMI, the highest sensitivity and NPV from all studied algorithms were observed for hs-TnT/mHS/copeptin (100%, 95% CI 96.6–100, and 100%, 95% CI 75.3–100). At 30 days, the highest event-free survival was achieved in patients stratified with hs-TnT/mHS/copeptin algorithm (100%) with 100% (95% CI 75.3–100) NPV and 100% (95% CI 96.6–100) sensitivity. Conclusions . The combination of baseline hs-TnT, copeptin, and the mHS has an excellent sensitivity and NPV for short-term risk stratification. Such approach might improve the triage system in emergency departments and be a bridge for inclusion to serial blood sampling algorithms.